List of persons restored to the roll of privateer pensioners - Edwards, James L., active 1837-1850.
List of persons restored to the roll of privateer pensioners, complete to November 17, 1848, signed by James L. Edwards, U.S. commissioner of pensions.
Public official and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection
Keywords: Army officers; Public officials